2013
DOI: 10.1111/tme.12011
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and transfusion in nonagenarians undergoing emergency, non‐traumatic surgery: a prospective observational study

Abstract: The independent transfusion predictors in nonagenarians should be taken into account for cross-matching. Transfusional policy being similar between nonagenarians and third-aged patients; the differences in thresholds were due to the differences in the populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Our participants were older, and more than half of them had been diagnosed with neoplasms as well. When looking at surgical populations or another study in our center with nonagenarians undergoing emergency procedures, the percentage is closer . On the other hand, our data suggest that preoperative Hb optimization was useful in most cases.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our participants were older, and more than half of them had been diagnosed with neoplasms as well. When looking at surgical populations or another study in our center with nonagenarians undergoing emergency procedures, the percentage is closer . On the other hand, our data suggest that preoperative Hb optimization was useful in most cases.…”
Section: Discussionmentioning
confidence: 73%
“…For patients undergoing moderate‐ to high‐risk surgery, our center implemented enhanced recovery programs, which include preoperative optimization of Hb levels. Despite the general transfusion guidelines in our hospital, the actual decision to administer RBCs depends entirely on the criteria of the attending physician, especially for high‐risk populations (such as premature babies and the fourth‐age patients), where there are no validated guidelines or evidence‐based protocols. To audit our transfusion practice, we recorded baseline and postoperative Hb concentrations as well as the transfusion threshold (defined as the lowest Hb value registered before the first transfusion).…”
Section: Methodsmentioning
confidence: 99%
“…21 However, anemia had no significant impact on morbidity or mortality. 21 Overall, there is strong evidence of correlations between anemia and a range of clinical outcomes. However, the panel acknowledged that anemia is not a confirmed cause of these outcomes; it is possible that anemia is a marker of other underlying morbidities that impair outcomes.…”
Section: Supporting Evidence: Outcomesmentioning
confidence: 99%
“…Two Austrian benchmark studies, conducted in cardiac, orthopedic, and abdominal surgery, showed that the preoperative Hb level was one of the main predictors of RBC transfusion 19,20. In a study of nonagenarians undergoing nonelective, nontrauma-related surgery, preoperative anemia was shown to be an independent risk factor for RBC transfusion 21. However, anemia had no significant impact on morbidity or mortality 21…”
Section: Consensus Statementsmentioning
confidence: 99%
See 1 more Smart Citation